JQ1, a bromodomain inhibitor, suppresses Th17 effectors by blocking p300‐mediated acetylation of RORγt. (23rd March 2020) - Wang, Xiunan; Yang, Yan; Ren, Dandan; Xia, Yuanyuan; He, Wenguang; Wu, Qingsi; Zhang, Junling; Liu, Miao; Du, Yinan; Ren, Cuiping; Li, Bin; Shen, Jijia; et al.
Abstract : Background and Purpose: Th17 cells play critical roles in chronic inflammation, including fibrosis. Histone acetyltransferase p300, a bromodomain‐containing protein, acetylates RORγt and promotes Th17 cell development. The bromodomain inhibitor JQ1 was shown to alleviate Th17‐mediated pathologies, but the underlying mechanism remains unclear. We hypothesized that JQ1 suppresses the response of Th17 cells by impairing p300‐mediated acetylation of RORγt. Experimental Approach: The effect of JQ1 on p300‐mediated acetylation of RORγt was investigated in HEK293T (overexpressing Flag‐p300 and Myc‐RORγt) and human Th17 cells through immunoprecipitation and western blotting. To determine the regions of p300 responsible for JQ1‐mediated suppression of HAT activity, we performed HAT assays on recombinant p300 fragments with/without the bromodomain, after exposure to JQ1. Additionally, the effect of JQ1 on p300‐mediated acetylation of RORγt and Th17 cell function was verified in vivo, using murine Schistosoma ‐induced fibrosis models. Liver injury was assessed by histopathological examination and measurement of serum enzyme levels. Expression of Th17 effectors was detected by qRT‐PCR, whereas IL‐17‐ and RORγt‐positive granuloma cells were detected by FACS. Key Results: JQ1 impaired p300‐mediated RORγt acetylation in human Th17 and HEK293T cells. JQ1 failed to suppress the acetyltransferase activity of p300 fragments lacking the bromodomain. JQ1 treatment attenuated Schistosoma ‐induced fibrosis in mice, by inhibiting RORγt acetylation and IL‐17 expression. Conclusions and Implications: JQ1 impairs p300‐mediated RORγt acetylation, thus reducing the expression of RORγt target genes, including Th17‐specific cytokines. JQ1‐mediated inhibition of p300 acetylase activity requires the p300 bromodomain. Strategies targeting p300 may provide new therapeutic approaches for controlling Th17‐related diseases.